Danger along the high road: report from the 2017 field season of the Vayots Dzor Fortress Landscapes Project (VDFLP), Armenia - Earley-Spadoni, Tiffany; Petrosyan, Artur; Gasparyan, Boris (ARAMAZD: Armenian Journal of Near Eastern Studies, 2019)
The Vayots Dzor Fortress Lansdscapes Project investigates the rise and fall of fortress culture in southern Armenia, focusing on the Late Bronze/Early Iron and medieval periods. The paper summarises the findings of the inaugural field season in 2017. The team performed extensive and intensive survey in a high alpine valley that was a key transportation corridor between Lake Sevan in the north and Nakhichevan and northwest Iran to the south. The project employed digital mapping, drone photogrammetry and digital storytelling in support of digital humanities approaches. Important findings include the documentation of Late Bronze/Early Iron cyclopean fortress architecture situated along roads as well as evidence for Urartian control of the valley. Furthermore, medieval structures and monuments are prominent features in the archaeological record of the valley.